Freedom Learning In the Middle of the Covid-19 Pandemic - Wahib, Ahmad (Jurnal Paradigma, 2022)
The “Merdeka Belajar” program, if linked to the Merdeka Learning Program initiated by the Minister of Education and Culture of the Republic of Indonesia, is a free choice that can be given to students to suit their interest and character. Some teachers apply coservative teaching methods. They provide step by step instructions so that both students and studentas are like being bribed with a spoon. In fact, everyone has a different way of learning. The pandemic has been able to paralyze various sectors. One of those affected is the education sector. The arrival of the corona has caused the world of education to be closed at home. Work form home (WFH) is the best solution so that educational activities can continue.